Bioimpedance analysis is not superior to clinical assessment in determining hydration status: a prospective randomized-controlled trial in a Western dialysis population - Sommerer, Claudia; Felten, Paul Thomas; Toernig, Johannes; Zeier, Martin; Dikow, Ralf (Hemodialysis international, 2021)
Introduction Fluid management is an important goal of dialysis treatment. The accurate assessment of fluid status is still a challenge for clinical nephrologists. Bioimpedance analysis (BIA) has been proposed as an objective tool to assess hydration. Methods This was a prospective randomized controlled study to compare hydration status measured by clinical assessment compared to BIA using a body composition monitor (BCM). The primary outcome was defined as the decline of cardiac biomarker N-terminal pro brain natriuretic peptide (NT-proBNP) from baseline to the end of the study. Findings About 281 chronic hemodialysis patients were assessed for eligibility, and 132 patients provided written informed consent to participate (65 BIA group, 67 clinical group). Predialytic NT-proBNP, and decline of NT-proBNP were similar in both groups. The amount of overhydration (2.18 ± 2.11 L vs. 1.29 ± 1.97 L; p 0.016) and the number of patients with severe overhydration (46.0% vs. 30.6%, p = 0.04) were significantly higher in the BIA group at the end of the study. Fluid accumulation in the interdialytic period was significantly lower in the clinical group (p = 0.013). Adverse events occurred more often in the BIA group (p = 0.032). The cumulative number of hypovolemic events was significantly higher in the BIA group (p = 0.002). Discussion Fluid management by BIA does not lead to a better cardiac outcome (appraised by surrogate markers) than fluid management by careful clinical assessment. Adapting the dry weight according to BIA results increases the risk of adverse events, especially hypovolemic episodes. Careful clinical fluid assessment is important for optimal care of chronic hemodialysis patients.
Gesehen am 05.09.2023